Electrical characterization of lanthanum-modified bismuth titanate thin films obtained by the polymeric precursor method - Simoes, A. Z.; Stojanovic, B. D.; Zaghete, M. A.; Riccardi, C. S.; Ries, A.; Moura, F.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Taylor & Francis Ltd, 2004)
Lanthanum-modified bismuth titanate, Bi4-xLaxTi3O12 (BLT), thin films with a La concentration ranging from 0 to 0.75 were grown on Pt/Ti/SiO2/Si substrates using a polymeric precursor solution and spin-coating method. The scanning electron microscopy shows a change of morphology with increasing the lanthanum concentration. The BLT films show well-saturated polarization-electric field curves whit remnant polarizations of 14.7, 20.5, 21.5, and 20.4 muC/cm(2) for x = 0, 0.25, 0.50 and 0.75, respectively. The dielectric constant of BLT (x = 0.75 mol% La) is equal to 158 while dielectric loss remain low (tandelta = 0.0018).
Keywords: BLT; thin films; electrical properties